2012
DOI: 10.1029/2012wr012449
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm shift in understanding and quantifying the effects of forest harvesting on floods in snow environments

Abstract: [1] A well-established precept in forest hydrology is that any reduction of forest cover will always have a progressively smaller effect on floods with increasing return period. The underlying logic in snow environments is that during the largest snowmelt events the soils and vegetation canopy have little additional storage capacity and under these conditions much of the snowmelt will be converted to runoff regardless of the amount or type of vegetation cover. Here we show how this preconceived physical unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(105 citation statements)
references
References 82 publications
5
97
2
Order By: Relevance
“…Stream responses to storms showed significant changes after HWA infestation for only extreme events, partially supporting our second hypothesis. Even with vigorous statistical analysis and the large sample sizes used in this study, making inferences from such results must be performed cautiously, especially when the only observed differences are at the tails of the distribution (Alila et al ., ; Green and Alila, ). However, several observations suggest that the changes observed in the extreme storms are physically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Stream responses to storms showed significant changes after HWA infestation for only extreme events, partially supporting our second hypothesis. Even with vigorous statistical analysis and the large sample sizes used in this study, making inferences from such results must be performed cautiously, especially when the only observed differences are at the tails of the distribution (Alila et al ., ; Green and Alila, ). However, several observations suggest that the changes observed in the extreme storms are physically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of flow frequency changes other than for completely cleared conditions (Figure b) was not performed in this study because of inherent methodological limitations. First, the 10‐year recurring meteorological data series used in this study lacks extreme flow events, and larger floods were shown to be more sensitive landcover changes when assessed by FP in snow‐dominated environments (Green and Alila, ). As noted in Alila et al (), the frequency analysis itself depends strongly on sample size, climate, and watershed physiography.…”
Section: Discussionmentioning
confidence: 99%
“…Our calculated changes in maximum daily yield-including chronological pairings-were compared to changes derived using frequency pairing of modelled flows generated from UPC data by Green and Alila (2012) and Schnorbus and Alila (2013). The interaction term was considered significant when p ≤ .05.…”
Section: Paired Watershed Approachmentioning
confidence: 99%
“…Summarizing research from a broad range of snowmeltdominated watersheds, Bosch and Hewlett (1982) also suggest that changes in annual yield following vegetation removal only occur in areas where annual precipitation exceeds~500 mm. Research also shows that internal watershed processes can affect streamflow response, while local climate conditions can affect both the magnitude and duration of that response (Biederman et al, 2015;Green & Alila, 2012;Zhao, Zhang, Xu, & Scott, 2010). These small or undetectable changes were thought to be due either to drier soils and lower runoff generation in areas with less precipitation or to desynchronisation of snowmelt runoff from disturbed and undisturbed areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation